A Balancing Act: Agency and Constraints in University Students’ Understanding of and Responses to Sexual Violence in the Night-Time Economy - Anitha, Sundari (Violence against women, 2021)
This article extends our understanding of how university students make sense of, and respond to, sexual violence in the night-time economy (NTE). Based on semi-structured interviews with 26 students in a city in England, we examine students’ constructions of their experiences of sexual violence within the NTE, exploring their negotiations with, and resistance to, this violence. Building upon theories of postfeminism, we interrogate the possibilities for resistance within the gendered spaces of the NTE and propose a disaggregated conceptualization of agency to understand responses to sexual violence, thereby offering useful insights for challenging sexual violence in the NTE and in universities.